Writing the Digital History of Nazi Germany Potentialities and Challenges of Digitally Researching and Presenting the History of the Third Reich, World War II, and the Holocaust - Timpe, Julia; Buda, Frederike (De Gruyter, 2022)
This book will consider how the outcomes of "doing history digitally" include different kind of sources and data, as well as new ways of researching historical questions, and innovative forms of presenting history. All contributions focus on aspects related to the history of National Socialism, World War II and the Holocaust.